Temperature responses of two synergistic pathways for low-temperature catalytic oxidation of high-concentration NO over ACFs: Nano-confinement and nitrogen-containing groups. (1st October 2022) - Zhang, Runcao; Gao, Fengyu; Tang, Xiaolong; Yi, Honghong; Zhou, Yuansong
Graphical abstract: Abstract: This study reveals for the first time that low-temperature catalytic oxidation of high-concentration NO over ACFs achieved by two synergistic paths: the quasi-homogeneous NO oxidation (path 1) and the nitrogen-containing functional groups catalysis (path 2). In path 1, the kinetic properties of reaction transition state are stabilized by ultra-micropores due to its non-specific van der Waals interaction, accelerating the transfer from gaseous reactants to the transition state 100 ∼ 1000 times. The micropore confinement effect of activation enthalpy is strongest at ambient temperature therefore the catalytic efficiency is the highest 6.89 × 10 -4 mol·L -1 ·S -1 . In path 2, extra π electrons generated by the substitution of N for C in the aromatic ring transfer to NOx and O2 . Pyridine and quaternary nitrogen serve as catalytical active sites to promote the adsorption of NO and the activation of O2 . Temperature increasing leads to a significant negative entropy barrier, the catalytic activity decreases accordingly, this is the main reason for the fluctuation in NO oxidation efficiency caused by temperature. The approximate proportion of the two oxidation pathways and their changes with reaction temperature are quantitatively analyzed by transition state theory calculations. Raising the reaction temperature from 25℃ to 200℃ increased the activity contribution of the active functional group catalytic pathway by about 25 %, which to some extent compensated for the negative entropy barrier effect of the quasi-homogeneous NO oxidation pathway.